Boosted selective catalytic nitrate reduction to ammonia on carbon/bismuth/bismuth oxide photocatalysts. (10th January 2022) - Hao, Derek; Wei, Yunxia; Mao, Liang; Bai, Xiaojuan; Liu, Yang; Xu, Bentuo; Wei, Wei; Ni, Bing-Jie
Abstract: Using solar energy to catalytically convert nitrate into ammonia is attractive for waste recycling and sustainable development. However, the rapid recombination of electron-hole pairs and the poor selectivity are obstructing photocatalytic nitrate reduction to ammonia to be mass applied currently. In this work, we reported a facile synthesis of carbon/bismuth/bismuth oxide photocatalyst via a one-pot hydrothermal reaction without using reducing reagent. Compared with α-bismuth oxide (α-Bi2 O3 ), the photocatalytic ammonia yield of the optimum sample increased 3.65 times. In addition, the ammonia selectivity increased from 65.21% to 95.00%. The highly enhanced photocatalytic performance was attributed to the surface plasmon resonance of metallic bismuth. Meanwhile, the formation of carbon enables to boost the transfer of electrons significantly. Under light irradiation, electrons can be accumulated on metallic bismuth, effectively boosting the reduction of nitrate. The findings of this work will contribute to the recycling of nitrate for ammonia synthesis and sustainable environmental development. Graphical abstract: Image 1 Highlights: A carbon/bismuth/Bi2 O3 photocatalyst prepared via a one-pot hydrothermal reaction. The composites exhibited efficient NO3 − reduction to NH3 with high selectivity. The mechanism for the enhanced photocatalytic activity was studied.